Product Packaging, Brand Equity, and Customer Experience as Drivers of Wardah Loyalty - Wenti Ayu Sunarjo; Siti Nurhayati; Jihan Karimatus Sa`Diyyah (International Journal of Management, Economic, Business and Accounting, 2026)
Purpose of the study — This study evaluates the comparative associations of product packaging, brand equity, and customer experience with customer loyalty toward Wardah, a halal-positioned cosmetic brand, among consumers in Pekalongan City. Research Method: An explanatory cross-sectional survey was administered through Google Forms to 100 purposively selected Wardah users aged 17–45 years who had purchased or used the products at least three times. The data were analyzed using multiple linear regression in SPSS version 23. Result— The regression model was significant (F = 34.131, p < .001) and explained 51.6% of the variance in customer loyalty (adjusted R² = .501). Product packaging (β = .326, p = .001), brand equity (β = .314, p = .004), and customer experience (β = .188, p = .045) were positively associated with loyalty. Conclusion— Packaging was the strongest predictor, closely followed by brand equity, while customer experience retained a smaller positive association. Wardah should combine functional packaging improvements, consistent brand meaning, and coordinated customer touchpoints to sustain repeat purchase and advocacy. Limitations: The non-probability, single-city, single-brand, cross-sectional design and the concentration of young female respondents restrict generalization and causal interpretation. Contribution: The study compares functional, symbolic, and experiential loyalty drivers in one model and provides locally grounded evidence from consumers of an Indonesian halal-positioned cosmetic brand.